Data-driven analysis of influence between radiologists for diagnosis of breast lesions - Fu, Chao; Wang, Dongyue; Chang, Wenjun (Annals of operations research, 2023)
Breast lesions are the most common threat to the health of women. The accumulation of historical examination reports for diagnosing breast lesions in clinical practice provides the necessary foundations for analyzing the diagnostic preferences of radiologists and the mutual influence between radiologists in a hospital. This mutual influence is important for indicating the development of an ultrasonic department in which radiologists work. To conduct a data-driven analysis of the influence between the two radiologists, the influence of the diagnostic preferences of one radiologist on the other was qualitatively defined using regression models. Following the qualitative definition, the process of analyzing the influence between two radiologists was designed, in which ten machine learning regression algorithms were included to make a reliable analysis. A statistical comparison method was developed using each machine learning regression algorithm to generate the indicator pair. The indicator pairs generated by ten machine learning regression algorithms were integrated using absolute majority voting to derive the overall indicator pair, from which the influence between two radiologists was determined, namely the unclear influence, clear influence, or significant influence. Experiments were conducted based on historical examination reports collected from two hospitals in Hefei, Anhui, China. The experimental results indicate that the trend in the influence between two radiologists in one hospital is different from that in the other hospital, which is associated with the management pattern, innovation incentive, and reward pattern of the two hospitals. A general conclusion on managerial insights was drawn to generalize the findings of this study.